Monograph review by Kit O. I., Shaposhnikov A. V. General carcinogenesis. Exogenous tumorogenic effects. Rostov-on-Don: LLC "Don Publishing House"; 2022, 128 p. - A. Yu. Abrosimov (Южно-Российский онкологический журнал)
The second part of a three-component work on gen- eral carcinogenesis has been published. The first part (2021) deploys modern theories, models of general carcinogenesis: mutation theory, models of genomic instability, Darwinian and non-genotoxic models, and also explains the roles of inflammation, immunological devi- ations and tumor microenvironment in carcinogenesis.